Irrigação por gotejamento subsuperficial na produção e qualidade de cana-de-açúcar - Dalri, Alexandre Barcellos; Cruz, Raimundo Leite [UNESP]; Garcia, Carlos Jesus Baca; Duenhas, Luiza Helena (My University, 2008)
In Brazil, sugarcane is mostly cropped in dry land conditions. However, it is known that irrigation is present in advanced agriculture, because of its higher yields, better product quality and rainfall independence. This work aimed to study subsurface drip irrigation frequencies on sugarcane development during the first season. Treatments were defined by different irrigation frequencies: irrigation system were turned on when evapotranspiration reached 10 mm, 20 mm, and 30 mm, for treatments L 1, L 2, and L 3, respectively. Treatment L 0 was defined as control (non-irrigated). It was observed that subsurface drip irrigation did not affected sugarcane quality and there was no statistical difference among different irrigation frequencies for yield. However, when compared to the control, treatments L 1, L 2 and L 3 showed yield increase of 47.33%, 58.53%, and 39.86%, respectively.
Subsurface drip irrigation on sugarcane yield and quality
Keywords: Irrigation frequency; Irrigation management; Technological analysis; Evapotranspiration; Irrigation; Statistical methods; Sugar cane; Agricultural technology; Crop yield; Drip irrigation; Food quality; Irrigation system; Water management; Water treatment; Brazil; South America